Comparative effectiveness of bariatric surgeries in patients with type 2 diabetes mellitus and BMI≥25kg/m2: a systematic review and network meta-analysis - Maria Neves Carmona (2021)
Purpose: In patients with type 2 diabetes mellitus (T2DM), bariatric surgery appears to be more effective than medical treatment (MT) at improving glycaemic control and decreasing cardiovascular risk. However, long-term effectiveness has not been systematically assessed. In this study, we aimed to systematically assess randomized controlled trials, with at least 5 years of follow-up, on bariatric surgery in patients with T2DM and BMI≥25kg/m2, as well as to compare different bariatric procedures. Material and methods: PubMed, SCOPUS and Web of Science were searched. We performed a network meta-analysis to evaluate the comparative effectiveness of the different procedures and MT in terms of full T2DM remission, weight loss, complications, and cardiometabolic biomarkers. The quality of evidence was assessed using the Cochrane Risk of Bias Tool and CINeMA. Results: We included 10 primary studies. Laparoscopic one-anastomosis gastric bypass (LOAGB) was found to be a more effective treatment for T2DM than the remaining procedures (I2=0, inconsistency p-value=0.861). Biliopancreatic diversion without duodenal switch was found to be more effective than laparoscopic Roux-en-Y gastric bypass and laparoscopic adjustable gastric banding regarding percent total cholesterol and low-density lipoprotein change. Regarding percent high-density lipoprotein and weight change, all analysed surgical treatments were shown to be more effective than MT. The confidence rating in our results was overall moderate, but most studies had high risk of performance and detection bias. Conclusion: Bariatric surgery, especially LOAGB, seems to be effective for T2DM remission. Nevertheless, more studies with longer follow-up times are needed to comprehensively assess bariatric surgery in T2DM.